The early postpartum period – Differences between women with and without a history of depression. (April 2021) - Schnakenberg, Patricia; Jo, Han-Gue; Stickel, Susanne; Habel, Ute; Eickhoff, Simon B.; Brodkin, Edward S.; Goecke, Tamme Weyert; Votinov, Mikhail; Chechko, Natalia
Abstract: Depression is a highly recurrent disorder. When in remission, it affords an important opportunity to understand the state-independent neurobiological alterations, as well as the socio-demographic characteristics, that likely contribute to the recurrence of major depressive disorder (MDD). The present study examined 110 euthymic women in their early postpartum period. A comparison was made between participants with ( n  = 20) and without ( n  = 90) a history of MDD by means of a multimodal approach including an fMRI experiment, assessment of hair cortisol concentration (HCC) and a clinical anamnestic interview. Women with a personal history of MDD were found to have decreased resting-state functional connectivity (RSFC) between the lateral parietal cortex (LPC) and the posterior cingulate cortex (PCC), and their Edinburgh Postnatal Depression Scale (EPDS) scores were significantly higher shortly after childbirth. More often than not, these women also had a family history of MDD. While women with no history of depression showed a negative association between hair cortisol concentration (HCC) and gray matter volume (GMV) in the medial orbitofrontal cortex (mOFC), the opposite trend was seen in women with a history of depression. This implies that women with remitted depression show distinctive neural phenotypes with subclinical residual symptoms, which likely predispose them to later depressive episodes. Highlights: A history of depression is one of the main risk factors for a new depressive episode Shortly after birth, women with a history of depression show higher depression scores Women with a history of depression show reduced RSFC between the LPC and the PCC The relationship between HCC and GMV of mOFC varies depending on previous depression